Advancing Spanish Speech Emotion Recognition: A Comprehensive Benchmark of Pre-Trained Models - Alex Mares; Gerardo Diaz-Arango; Jorge Perez-Jacome-Friscione; Hector Vazquez-Leal; Luis Hernandez-Martinez; Jesus Huerta-Chua; Andres Felipe Jaramillo-Alvarado; Alfonso Dominguez-Chavez (Applied Sciences)
Feature extraction for speech emotion recognition (SER) has evolved from handcrafted techniques through deep learning methods to embeddings derived from pre-trained models (PTMs). This study presents the first comparative analysis focused on using PTMs for Spanish SER, evaluating six models—Whisper, Wav2Vec 2.0, WavLM, HuBERT, TRILLsson, and CLAP—across six emotional speech databases: EmoMatchSpanishDB, MESD, MEACorpus, EmoWisconsin, INTER1SP, and EmoFilm. We propose a robust framework combining layer-wise feature extraction with Leave-One-Speaker-Out validation to ensure interpretable model comparisons. Our method significantly outperforms existing state-of-the-art benchmarks, notably achieving scores on metrics such as F1 on EmoMatchSpanishDB (88.32%), INTER1SP (99.83%), and MEACorpus (92.53%). Layer-wise analyses reveal optimal emotional representation extraction at early layers in 24-layer models and middle layers in larger architectures. Additionally, TRILLsson exhibits remarkable generalization in speaker-independent evaluations, highlighting the necessity of strategic model selection, fine-tuning, and language-specific adaptations to maximize SER performance for Spanish.